Characterizing the deformation, failure, and water-conducting fractures evolution of shallow weakly cemented overburden under coal mining - Li, Zhenhua; Zhang, Yandong; Gao, Xuefeng; Ma, Dan; Fan, Limin; Li, Guodong; Li, Xiaolei; He, Min; Cheng, Zheng (Frontiers in Earth Science, 2025)
Understanding the collapse mechanisms of shallow, multi-layered, weakly cemented overburden is key to safe and efficient coal mining in central and western China. Hence, we conducted a meter-scale similar physical model experiment using high-resolution digital speckle technology to replicate the deformation and failure patterns of shallowly buried, weakly cemented overburden under mining activities, and to determine the initiation, development, and stability of water-conducting fractures. Additionally, a site-scale numerical model was developed to allow for the examination of the stress-displacement evolution within the weakly cemented overburden. The results indicate that the maximum vertical displacements at key locations such as the basic roof, the weakly cemented critical layer, and the surface were 8.9 m, 8.65 m, and 8.2 m, respectively. The collapse step distance of the basic roof was 22.4 m, and the maximum collapse height reached 48 m. After the weakly cemented critical layer failed, the overlying strata collapsed accordingly, with the actual water-conducting fracture zone reaching a maximum height of 96.3 m. After the completion of coal mining, the overburden experienced four periodic collapses. As the working face advanced, the overburden in the center of the mined-out area showed a state of stress release, while the overburden on both sides exhibited stress concentration. The maximum vertical stresses in the siltstone and sandstone were 6.7 MPa and 1.9 MPa, with stress concentration factors of 2.2 and 0.6, respectively. This study provides valuable insights into the safety management of weakly cemented overburden.